2017
DOI: 10.1103/physreva.96.043403
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of Rydberg wave packets in the tunneling regime

Abstract: In the tunneling regime for strong laser field ionization of atoms, experimental studies have shown that a substantial fraction of atoms survive the laser pulse in many Rydberg states. To explain the origin of such trapping of population into Rydberg states, two mechanisms have been proposed : the first involves AC-Stark-shifted multiphoton resonances and the second, called frustrated tunneling ionization, leads to the recombination of tunneled electrons into Rydberg states. We use a very accurate spectral met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 30 publications
(43 reference statements)
3
22
0
1
Order By: Relevance
“…Since the energies of the Rydberg states are near the threshold so that their Stark shifts are all close to the Stark shift U p of the continuum, multiphoton resonance between the Rydberg and the initial states occurs at intensities that are separated by ∆U p = ω [1]. In addition, the dipole selection rule only allows even-order (odd-order) multiphoton transitions between states of equal (opposite) parity, which gives rise to a ∆U p = 2 ω separation between consecutive peaks for a transition between two states with specified parity [17,19]. Apparently, these features are beyond the scope of the semiclassical picture of the RSE.…”
Section: Comparison Of Tdse and Model Calculationsmentioning
confidence: 96%
“…Since the energies of the Rydberg states are near the threshold so that their Stark shifts are all close to the Stark shift U p of the continuum, multiphoton resonance between the Rydberg and the initial states occurs at intensities that are separated by ∆U p = ω [1]. In addition, the dipole selection rule only allows even-order (odd-order) multiphoton transitions between states of equal (opposite) parity, which gives rise to a ∆U p = 2 ω separation between consecutive peaks for a transition between two states with specified parity [17,19]. Apparently, these features are beyond the scope of the semiclassical picture of the RSE.…”
Section: Comparison Of Tdse and Model Calculationsmentioning
confidence: 96%
“…Theoretical analysis of the angular momentum distribution in the populated Rydberg states is less advanced. Predictions of Floquet theory for a monochromatic laser field [35] and results of numerical calculations for laser pulses with a trapezoidal envelope [32] yield that the angular momentum of the excited Rydberg states has the same parity as N p − 1, where N p is the minimum number of photons needed to ionize the atom. Furthermore, the angular quantum number of the states with the largest population in numerical calculations [9,10,32] agrees well with semiclassical estimations [36], initially performed for low-energy angular resolved photoelectron distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent theoretical studies of the excitation mechanism in strong fields mainly consider the distribution of the population as a function of the principal quantum number of the excited states [9,10,25,31,32]. It was shown that the modulation of the excitation probability is related to the channel closing effect [9,10,32,35]. The latter phenomenon occurs at threshold intensities at which the absorption of one more photon is needed to ionize the atom due to the shift of the ionization threshold by the ponderomotive energy.…”
Section: Introductionmentioning
confidence: 99%
“…As briefly described in [25], our numerical method to solve the TDSE is based on a spectral method, which consists in expanding the total wave function in a basis composed of products of spherical harmonics and complex radial Coulomb Sturmian functions. These Sturmian functions depend on a nonlinear parameter which allows one to monitor the region of the bound state spectrum we want to describe accurately.…”
Section: Numerical Aspectsmentioning
confidence: 99%
“…This is the objective of the present paper. Several attempts have been made to study this problem by solving numerically the time dependent Schrödinger equation (TDSE) [20,21,25]. However, such a calculation is tremendously difficult and still out of reach in the limit where the frequency tends to zero.…”
Section: Introductionmentioning
confidence: 99%